Altered Frequency-Dependent Brain Activation and White Matter Integrity Associated With Cognition in Characterizing Preclinical Alzheimer’s Disease Stages - Wang, Siyu; Rao, Jiang; Yue, Yingying; Xue, Chen; Hu, Guanjie; Qi, Wenzhang; Ma, Wenying; Ge, Honglin; Zhang, Fuquan; Zhang, Xiangrong; Chen, Jiu (Frontiers in Human Neuroscience, 2021)
Background: Subjective cognitive decline (SCD), non-amnestic mild cognitive impairment (naMCI), and amnestic mild cognitive impairment (aMCI) are regarded to be at high risk converting to Alzheimer’s disease (AD). Amplitude of low-frequency fluctuations (ALFF) can reflect functional deterioration while diffusion tensor imaging (DTI) is capable of detecting white matter integrity. Our study aimed to investigate the structural and functional alterations to further reveal convergence and divergence among SCD, naMCI, and aMCI and how these contribute to cognitive deterioration. Methods: We analyzed ALFF under slow-4 (0.027-0.073Hz) and slow-5 (0.01-0.027Hz) band and white matter fiber integrity among normal controls (CN), SCD, naMCI and aMCI groups. Correlation analyses were further utilized among paired DTI alteration, ALFF deterioration and cognitive decline. Results: For ALFF calculation, ascended ALFF values were detected in lingual gyrus (LING) and superior frontal gyrus (SFG) within SCD and naMCI patients respectively. Descended ALFF values were presented mainly in LING, SFG, middle frontal gyrus, and precuneus in aMCI patients compared to CN, SCD and naMCI groups. For DTI analyses, white matter alterations were detected within uncinate fasciculus (UF) in aMCI patients and within superior longitudinal fasciculus (SLF) in naMCI patients. SCD patients presented alterations in both fasciculi. Correlation analyses revealed that majority of these structural and functional alterations were associated with complicated cognitive decline. Besides, UF alterations were correlated with ALFF deterioration in SFG within aMCI patients. Conclusions: SCD shares structurally and functionally deteriorative characteristics compared with aMCI and naMCI, and tends to covert to either of them. Furthermore, abnormalities in white matter fibers may be the structural basis of abnormal brain activation in preclinical AD stages. Combined together, it suggests that structural and functional integration may characterize the preclinical AD progression.